A construção social da qualidade na produção agroalimentar: o caso do arroz "Amigo do Taim"1 - Flávio Sacco dos Anjos; Gisela Loureiro Duarte (Ciências Sociais Unisinos)
The article analyzes the trajectory that culminated in the creation of organic rice "Amigo do Taim", revealing the nature ofthe social ties that were being woven to develop a unique process of social construction of quality in a specifíc region ofRio Grande do Sul, in the close to one ofthe main natural reserves of this Brazilian state, the Taim Ecological Sta-tion. The initiative came amid the search for economic viability for a group of families settled in the extreme south of the state of Rio Grande do Sul. The project was led by a non-governmental organization that simultaneously proposed to establish a sustainable way ofusing natural resources in an area considered as buffer zone ofthe Taim ecological reserve. However, the project undergoes profound changes over time, amid the progressive abandonment ofthe project by the families involved due to the lack ofinstitutional sup-port, bureaucratic obstacles and the demobilization ofthe settlers. The space left by them is being occupied by medium producers. The case in point is inserted, from the theoretical point of view, in the great debate about the risks of conventional organic production.